Transparansi dan Keadilan dalam Pembagian Harta Waris Menurut Hukum Islam di Era Modern - Ahmad Fandika; Octa Fio Dila; Dwi Noviani (Student Scientific Creativity Journal, 2024)
This research examines the importance of transparency and fairness in the distribution of inheritance according to Islamic law in the modern era. The main problem faced is dissatisfaction and conflict between heirs due to unfair and non-transparent distribution. The purpose of this research is to identify how the principles of transparency and fairness can be applied in the distribution of inheritance in accordance with Islamic law, in order to maintain harmony and justice in the family and society. The research method used is a qualitative approach with a literature study, which involves collecting data from various literatures related to Islamic inheritance law. The results showed that transparency can be achieved through clear documentation, open communication, and the use of technology to digitize inheritance documents. Fairness in inheritance distribution emphasizes that gender differences do not affect inheritance rights, with men and women having equally strong rights, although there are differences in the amount of shares received based on utility and need. In conclusion, applying the principles of transparency and fairness in the distribution of inheritance according to Islamic law is crucial to avoid conflicts and ensure justice in families and societies in the modern era.